Pengaruh Ekstrakurikuler Pramuka dan Minat Terhadap Keterampilan Berbicara - Anggraini, Riska; Setyowati, Eny; Putri, Nimas Permata (STKIP PGRI Ponorogo Press, 2025)
This study aims to find out: 1) the influence carries the extracurricular and not follows extracurricular scouts on speaking skills; 2) the influence of high interest and low interest on speaking skills; 3) the effect of scout extracurricular and interest on speaking skills. This research method is quantitative with an experimental approach and research design of treatment by level 2 x 2. This study sample is a seventh-grade student VII B and VII C of SMPN 2 Sudimoro in the 2022/2023 academic year. The sampling was carried out by purposive sampling technique. Data collection techniques using observation, interview, inquiries, and tests. Data analysis technique using two-way analysis test of variance (ANAVA). The result of hypothesis testing showed that: 1) there was an effect of extracurricular and not follows extracurricular scouts on speaking skills or get value sig. = 0,000 > 0, 05; 2) there is no effect of high and low interest on students speaking skills or getting value sig. = 0,102 > 0, 05; 3) there is no interaction of scout extracurricular and students interest in speaking skills or getting value sig. = 0,286 > 0, 05.